2015
DOI: 10.2169/internalmedicine.54.4075
|View full text |Cite
|
Sign up to set email alerts
|

Dose-adjusted Lenalidomide Combined with Low-dose Dexamethasone Rescues Older Patients with Bortezomib-resistant Multiple Myeloma

Abstract: Objective The aim of this study was to assess the safety and efficacy of lenalidomide (Len), with the dose adjusted according to the renal function, plus low-dose dexamethasone (Dex) in older patients with bortezomib (Bor)-resistant multiple myeloma (MM). Methods The study included 68 consecutive patients 70 years of age or older diagnosed with MM at our institute and ineligible for high-dose melphalan therapy plus autologous stem cell transplantation. Fifteen older patients with relapsed or refractory MM (RRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Lenalidomide, pomalidomide’s IMiD analog, is metabolized minimally and eliminated predominantly via urinary excretion in the unchanged form in humans, 16 resulting in dosage adjustments for patients with creatinine clearance (CrCl) <50 mL/min. 17 , 18 Pomalidomide is eliminated predominantly through renal excretion (~73% of the administered dose), with <3% of the administered dose excreted in urine as unchanged pomalidomide across all dose levels. 19 Thus, it is relevant to assess the influence of renal impairment on pomalidomide clearance and plasma exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Lenalidomide, pomalidomide’s IMiD analog, is metabolized minimally and eliminated predominantly via urinary excretion in the unchanged form in humans, 16 resulting in dosage adjustments for patients with creatinine clearance (CrCl) <50 mL/min. 17 , 18 Pomalidomide is eliminated predominantly through renal excretion (~73% of the administered dose), with <3% of the administered dose excreted in urine as unchanged pomalidomide across all dose levels. 19 Thus, it is relevant to assess the influence of renal impairment on pomalidomide clearance and plasma exposure.…”
Section: Introductionmentioning
confidence: 99%
“…β2-MG and creatinine level have important implications in renal function impairment, and can also reflect the tumor burden of MM patients. [19][20][21] Our results showed that D and M patterns had the highest β2-MG and creatinine levels and the lowest hemoglobin, which suggested that MM bone marrows of D or M patterns had more severe tumor burden than N and SP. The latest R-ISS stage incorporates cytogenetic abnormalities and elevated serum LDH based on the ISS stage.…”
Section: Discussionmentioning
confidence: 96%